Evaluasi Program Pelayanan Publik Mobil Perpustakaan Keliling dalam Meningkatkan Budaya Literasi Siswa-Siswi Kabupaten Bintan - Nur Kahana, Kartini; Ananda, Almar; Wilyanti, Dina (Policy, Law and Political Research Center, 2023)
Based on the objectives of the mobile library car public service program in improving the literacy culture of Bintan Regency students. The Regional Library and Archives Office conducts a mobile library car tour by visiting various schools. This study aims to determine the evaluation of the mobile library car public service program in improving the literacy culture of Bintan Regency students. This research uses qualitative research methods with a descriptive approach. The location of this research is at the Regional Library and Archives Office of Bintan Regency. The results and discussion show that to achieve the goal of increasing the literacy culture of Bintan Regency students, the District Library and Archives Office has implemented the public service program to schools and the reciprocity obtained results in positive things and hopes to come back to provide a forum for students.